Potencial de produção de biogás e energia na indústria de abate de frangos no Brasil - Malaggi, Michelle (2014)
The current paper had as an objective to calculate the amount of biogas being made by the Brazilian chicken slaughter companies and the biogas capacitance for producing energy. Some of the substantial data from this paper was gathered in partnership with a poultry agroindustry that served as standard basis. The company has a daily cull of 266 thousands chickens a day, with a treatment system based on the Canadian bio digestive model, which through anaerobic degradation produces biogas as a result. The chicken slaughter industry produces an average of 743,77 m3.day-1 of biogas meaning that, it generates 2,78 m3.day-1 per slaughtered animal. Which its electricity production is of 1,47 kWh. With this data and other ones taken from relevant readings, we were able to calculate that Brazil has a capability of producing 39.335,44 thousands m3.day-1 of biogas and generating 57.823,11 kWh of electricity. Proving to be possible the use of agro industrial residues to generate the agro energy, helping and relieving the Brazilian electric energy system, which is currently on a critical situation.